Development of electronic electronic student worksheet in islamic religious education subjects - Mahrini; Zubair Jeelani (Jurnal Ilmiah Profesi Guru (JIPG), 2025)
Despite the increasing use of digital learning media, studies focusing on the development of Electronic Student Worksheets for Islamic Religious Education using a continuous development model remain limited. This study aims to develop an Electronic Student Worksheet for Islamic Religious Education to enhance students’ independent learning at Karsa Mulya Vocational High School, Palangka Raya. The research employed a Research and Development approach using the DevOps model, which emphasises continuous and sustainable product development. Data were collected through observations and interviews with teachers and students as the basis for needs analysis. The Electronic Student Worksheet was developed using the Canva Pro application and includes learning objectives as well as various forms of assessment, such as multiple-choice questions, crossword puzzles, essays, and case studies. The feasibility test results indicated an evaluation score of 88% from the subject-matter expert and 86% from the media expert, categorised as very feasible. The findings confirm that the Electronic Student Worksheet effectively supports students’ independent learning during internship programmes. The novelty of this study lies in the application of the DevOps model in developing an Electronic Student Worksheet for Islamic Religious Education. These findings provide practical implications for teachers by offering an effective digital learning medium that supports independent learning in vocational high school contexts. Pengembangan media elektronik lembar kerja peserta didik dalam mata pelajaran pendidikan agama islam Penelitian ini dilatarbelakangi oleh masih terbatasnya kajian pengembangan Electronic Lembar Kerja Peserta Didik (E-LKPD) Pendidikan Agama Islam yang menerapkan model pengembangan berkelanjutan. Penelitian ini bertujuan untuk mengembangkan E-LKPD Pendidikan Agama Islam guna meningkatkan kemandirian belajar peserta didik di SMK Karsa Mulya Palangka Raya. Penelitian menggunakan pendekatan Research and Development (R&D) dengan menerapkan model DevOps. Data dikumpulkan melalui observasi dan wawancara sebagai dasar analisis kebutuhan. E-LKPD dikembangkan menggunakan Canva Pro dan dilengkapi tujuan pembelajaran serta berbagai bentuk penilaian, seperti pilihan ganda, teka-teki silang, esai, dan studi kasus. Hasil uji kelayakan menunjukkan skor 88% dari ahli materi dan 86% dari ahli media dengan kategori sangat layak. Temuan penelitian menunjukkan bahwa E-LKPD efektif mendukung kemandirian belajar peserta didik selama praktik kerja industri. Kebaruan penelitian terletak pada penerapan model DevOps dalam pengembangan E-LKPD Pendidikan Agama Islam.